Novel aminochromone derivative inhibits tumor growth on xenograft model of lung cancer in mice - Ekaterina V Blinova; Marina O Dudina; Irina R Suslova; Elena A Samishina; Dmitry S Blinov; Dmitry A Roshchin (Wolters Kluwer Medknow Publications, 2018)
2-Amino-4H-chromene derivatives possess anticancer property proved on different in vivo and in vitro models of malignancies such breast, nasopharyngeal, bladder, ovary carcinomas, astrocytoma, and osteosarcoma. We assumed it might be effective to apply one of the derivatives as promising approach to lung carcinoma treatment. to evaluate how novel 4-aryl substituted 2-amino-4H-chromene derivative AX-554 impacts tumor growth and progression, as well as possible mechanisms for anticancer effect development on in vivo patient-derived heterotopic xenograft model of lung carcinoma in mice. This was an experimental in vivo study. 40 nu/nu BALB/c female mice were randomly allocated into four equal groups: Intact, control, reference, and main group. Animals of three latter groups were ingrafted with human-derived lung adenocarcinoma. Antitumor and antimetastatic action of AX-554 novel aminochromone derivative as a substance were studied. Mice survival was registered. Kinase of anaplastic lymphoma (ALK), tubulin Beta-3 (TUBB3), and c-mesenchymal-epithelial transition (MET) concentrations in the prime tumor nodes homogenates were determined by quantitative enzyme-linked immunosorbent assay. Dannet's parametric criterion and the nonparametric exact Fisher test were used. The normality of the distribution was determined using ANOVA. The survival curve was analyzed using Gehan's criterion with the Yates's correction. Aminochromone derivative possesses an inhibitory effect on human lung adenocarcinoma transplanted into nu/nu BALB/c female mice, as well as significant antimetastatic activity. About 50 mg/kg/day AX-554 intragastric course increases animals' life expectancy of more than 3.3 times when compared with the control and induces remission in 60% of cases. The anticancer effect of the derivative is due to anti-ALK-mediated activation of tumor cells apoptosis and suppression TUBB3-dependent cell proliferation.